A Comparative Analysis of Pakistani and Indian Social Media Memes: Cultural Narratives and Social Understandings - Abbas, Zainib; Sheikh, Muhammad Ahmad; Mir, Basim; Farrukh, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2024)
This study investigates the sociological impact and linguistic characteristics of Pakistani and Indian memes, focusing on their occurrence on social media sites, and explores how these digital expressions influence cultural stories and public opinions. Employing content analysis, a diverse collection of memes were analyzed to identify themes, linguistic elements, and cultural references attached to the memes under study. Besides, the study seeks to uncover the distinctions between memes in Pakistan and India, their appeal to viewers, and their impact on and representation of social norms, political opinions, and cultural heritage. The study focuses on comprehending the language, humor, and visual elements used to effectively convey messages from memes in different countries. The research embraces cultural essence and offers a thorough examination of how memes influence public opinion and cultural narratives in Pakistan and India. The finding reveals that memes have evolved as powerful tools for social interaction, self-expression, and cultural commentary in digital networks. Study highlights the importance of memes in modern discourse and emphasizes to understand the symbolic meaning of memes for deeper knowledge in their sociological and dialectal aspects.